2013
DOI: 10.1073/pnas.1221489110
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions control product specificity of isoprenyl diphosphate synthases in the insect terpenoid pathway

Abstract: Isoprenyl diphosphate synthases (IDSs) produce the ubiquitous branched-chain diphosphates of different lengths that are precursors of all major classes of terpenes. Typically, individual shortchain IDSs (scIDSs) make the C 10 , C 15 , and C 20 isoprenyl diphosphates separately. Here, we report that the product length synthesized by a single scIDS shifts depending on the divalent metal cofactor present. This previously undescribed mechanism of carbon chainlength determination was discovered for a scIDS from juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 43 publications
4
79
0
1
Order By: Relevance
“…Dual-function GPPS/FPPS enzymes have been reported previously in other insects (12,29,30). In the horseradish leaf beetle, P. cochleariae, the GPP/FPP product ratio is affected by the divalent metal cofactor used in the assay (12). Using site-directed mutagenesis, a previous study has shown that two residues (indicated in bold) preceding the first aspartate-rich motif of the IDS from the aphid Acyrthosiphon pisum (ApisGPPS/FPPS, YQLVLDDIMD, at positions 194-203 of the alignment in Fig.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Dual-function GPPS/FPPS enzymes have been reported previously in other insects (12,29,30). In the horseradish leaf beetle, P. cochleariae, the GPP/FPP product ratio is affected by the divalent metal cofactor used in the assay (12). Using site-directed mutagenesis, a previous study has shown that two residues (indicated in bold) preceding the first aspartate-rich motif of the IDS from the aphid Acyrthosiphon pisum (ApisGPPS/FPPS, YQLVLDDIMD, at positions 194-203 of the alignment in Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In I. pini, the IPPI transcript is up-regulated by both juvenile hormone III and feeding in adults for pheromone biosynthesis (27,28). Dual-function GPPS/FPPS enzymes have been reported previously in other insects (12,29,30). In the horseradish leaf beetle, P. cochleariae, the GPP/FPP product ratio is affected by the divalent metal cofactor used in the assay (12).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations